PERANCANGAN APLIKASI E-LIBRARY BERBASIS MOBILE DI MTsN 6 AGAM - Diyan Rianti; Riri Okra; Hari Antoni Musril; Sarwo Derta (Jurnal Sistem Informasi dan Informatika (Simika), 2023)
The research conducted refers to the problems found when the authors made observations at MTsN 6 Agam.This is motivated by difficulties in handling queues during the process of borrowing books, the limitednumber of printed books in the library so that they cannot borrow and read books. There is limited time forborrowing books at the library and it takes quite a long time in the process of borrowing books. Given theseproblems, the authors designed a mobile-based e-Library application at MTsN 6 Agam. The purpose of thisresearch is to produce a mobile-based e-library application that can be used properly, practically, andeffectively. The author uses the “Research and Development”(R&D) or development method. Thedevelopment model used is the prototype. The results of this study are in the form of a mobile-based e-libraryapplication with the Android operating system that can be used by students and teachers wherever andwhenever they are. The results of the validity test were carried out by three expert examiners, namely expertsgetting a value of 0.91 with valid criteria, then the results of the practicality test conducted by two examiners,namely getting a score of 98% with very practical criteria. Furthermore, the results of the effectiveness testconducted by fifteen examiners, namely students at MTsN 6 Agam, obtained an average score of 0.89 witha very high category.